Analysis of cognition application in teaching and learning for early childhood by physical and aesthetic elements in National Standard Preschool Curriculum (KSPK) - Nachiappan, Suppiah; Makhtar, Norwahida (Journal of Research, Policy & Practice of Teachers and Teacher Education, 2018)
This study aimed to analyze the progress of cognition process through physical and aesthetic development elements in teaching and learning for pre-school teacher. The data was obtained through a practical experience in a private kindergarten located at Cheras, Kuala Lumpur. The daily lesson plans and student work sheets for two months duration were studied to obtain and transcribe data into texts. With the help of Hermeneutics method, the data were analyzed and showed that pre-school teachers were capable of planning the daily lesson and effective teaching methods according to the level of a child’s development. This research also showed how the pre-school teachers applied the cognition process in teaching and learning activities. Studies showed that the pre-school teachers lacked in creativity in planning the daily lesson, particularly involving the physical and aesthetic development. The teaching approach and methods that were less effective would cause the slow development in cognition process among pre-school students.